The Influence of Online Customer Reviews and Online Customer Ratings on Purchasing Decisions with Purchase Intention as a Mediating Variable (Case Study of Shopee Marketplace Users in Semarang Regency) - Dani, Anisa Eka Aprilia; Nurhayati, Nurhayati (Economics and Business International Conference Proceeding, 2024)
This research aims to analyze the influence of online customer reviews and online customer ratings on purchasing decisions with purchase interest as a mediating variable among Shopee marketplace users in Semarang Regency. The population in this research is shopee users in Semarang Regency. The number of samples used was 120 respondents. The sampling technique is non-probability sampling. Data collection methods using questionnaires and quantitative methods. Data analysis used descriptive analysis with SmartPLS 4 software. The results showed that a) online customer reviews had an effect on purchase interest, b) online customer ratings had an effect on purchase interest, c) purchase interest had an effect on purchasing decisions, d) online customer reviews had an effect on purchasing decisions, e) online customer ratings influence purchasing decisions.